Plant-pollinator interactions along the altitudinal gradient in Berberis lycium royle: An endangered medicinal plant of the Himalayan region - Nahila Anjum; Sajid Khan; Susheel Verma; Kailash S. Gaira; Balwant Rawat; Nakul Chettri; Mohd Hanief (PLoS ONE, 2025)
The terrestrial ecosystem, particularly mountain regions, influences species distribution by providing diverse climatic conditions that vary with rising altitude. These climatic factors play a significant role in determining species phenology and niche width. However, the environmental factors influencing pollination dynamics of specific plant species across altitudes remain unexplored. Considering the gaps, we assess how the composition and abundance of pollinator fauna associated with the important medicinal plant Berberis lyciumRoyle (Berberidaceae) vary across five distinct altitudinal gradients (800–2200 m) in the Pir-Panjal mountain range in the northwestern part of the Indian Himalayan region. Pollinators, including bees, butterflies, wasps, and flies were monitored over two consecutive flowering seasons (2022–2023). A total of 39 insect species representing five orders and 17 families, were recorded visiting B. lycium during its flowering period across the altitudinal range. The linear regression model indicated that all four pollination indices exhibited a declining trend with increasing altitude when data were pooled together. However, only foraging speed (FS) and index of visiting rate (IVR) were showed significant declines. Among individual pollinator groups, only Lepidoptera displayed a significant relationship with altitude, while other groups exhibited asynchrony along the altitudinal gradient. Furthermore, reproductive output (fruit and seed production) declined significantly with increasing altitude. Our findings suggest that while altitude influences species distribution but also differentially shapes plant-pollinator interactions, pollinator foraging behaviour, and reproductive success. This study highlights the importance of monitoring plant-pollinator interactions in fragile Himalayan ecosystem, where environmental changes could have cascading effects on ecological stability.